Outcome of autologous hematopoietic stem cell transplant in older patients with B cell lymphoma when selected for fitness and chemosensitive disease. (April 2019) - Lemieux, Christopher; Ahmad, Imran; Bambace, Nadia M.; Bernard, Léa; Cohen, Sandra; Delisle, Jean-Sébastien; Fleury, Isabelle; Kiss, Thomas; Mollica, Luigina; Roy, Denis-Claude; Sauvageau, Guy; Roy, Jean; et al.
Highlights: One of the largest older patients cohort undergoing autologous transplant for NHL. Toxicity and resource use are not different for patients ≥65 years old. Stable and chemo resistant disease at transplant are associated with poor outcomes. Treatment related mortality is only 1% at one year in this older patient cohort. Abstract: Background: Autologous hematopoietic stem cell transplantation (AHSCT) in the older population is associated with an increased risk of morbidity and mortality. Determination of the hematopoietic cell transplant comorbidity index (HCT-CI) has contributed to improve patient selection while allowing prediction of their non-relapse mortality (NRM). The goal of this study was to identify factors influencing both safety and efficacy of AHSCT in an older non-Hodgkin lymphoma (NHL) population to better select those who will benefit from this intervention in the Canadian context of a single-payer government healthcare program. Methods: This single center, retrospective study, examined clinical outcomes in 90 consecutive older patients (≥60 years old) with B-cell NHL treated with AHSCT between 2008 and 2014. Findings: Median age was 63 (60–69) at time of transplantation. The HCT-CI risk score was low, intermediate and high in 34%, 40% and 26% of patients, respectively. NRM was 1% at 100 days and one-year post transplant and not influenced by age. At a median follow-up of 52 months, median progression-free survival (PFS) was 56 months while median overall survival (OS) was still not reached. Stable and progressive disease status at time of transplantation were associated with a lower PFS (HR 2.94) and OS (HR 3.91). BEAC conditioning and a graft cell dose 5 × 10 6 CD34+/kg led to faster recovery, decreased toxicity and resource consumption. Interpretation: In the older population, AHSCT is safe and optimal when restricted to fit chemosensitive patients.